2010
DOI: 10.1108/13552541011025861
|View full text |Cite
|
Sign up to set email alerts
|

The effect of processing parameters on characteristics of selective laser sintering dental glass‐ceramic powder

Abstract: Purpose -The purpose of this paper is to report a study about the rapid prototyping method of dental glass-ceramic restoration. Design/methodology/approach -Dental glass-ceramic restoration materials have excellent physical and chemical, mechanical, aesthetic and biocompatibility characteristics. However, casting methods adopted at present have complicated procedures and high costs; the forming qualities are especially difficult to control. These problems greatly restrict their clinical application and promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 7 publications
0
44
0
Order By: Relevance
“…A lot of work has been done on ceramic composite materials. Examples include ceramic-glass composites [106][107][108][109][110][111] and ceramic-polymer composites. [112][113][114][115][116] Here, the low-melting glass/ polymer provides densification due to the liquid phase formation.…”
Section: Indirect Slsmentioning
confidence: 99%
“…A lot of work has been done on ceramic composite materials. Examples include ceramic-glass composites [106][107][108][109][110][111] and ceramic-polymer composites. [112][113][114][115][116] Here, the low-melting glass/ polymer provides densification due to the liquid phase formation.…”
Section: Indirect Slsmentioning
confidence: 99%
“…For instance, it was recently demonstrated that new nano‐glass‐ceramics with a notably high ZrO 2 content can be synthesized using sol‐gel methods . The technology required to achieve this goal could rely on chemistry‐based and applied nanotechnology. New or improved sintering/crystallization processes, such as microwave heating, laser crystallization, spark‐plasma sintering, biomimetic assemblage of crystals, textured crystallization, and electron beam crystallization, should be further developed. Chemical strengthening of RDGCs by ion exchange, as tested by Kawai et al and Fischer et al, is a promising route and should be further pursued. Glass‐ionomer composites are widely used in restorative dentistry. We believe that glass‐ceramic powders, including bioactive formulations, can also be used as inorganic fillers in these composite restoratives.…”
Section: Conclusion and Trendsmentioning
confidence: 99%
“…There are reports available in literature regarding the SLS processing of ceramics with different particle sizes and using different thermoplastics as sacrificial binders (Goodridge et al, 2006;Kruth et al, 2003;Leu et al, 2008;Liu et al, 2007Liu et al, , 2010Subramanian et al, 1995;Wohlert and Bourell, 1996). However, there is no previous report that showed how to reduce the binder content and particle size together with a consideration towards fabrication and post-processing issues.…”
Section: Introductionmentioning
confidence: 96%
“…The additive manufacturing (AM) techniques have an advantage of being able to tailor the shape and internal architecture of the scaffolds, providing an alternative approach for such biomedical applications (Kruth et al, 1998). The two AM methods that are widely used for bone tissue engineering are: (i) extrusion based, including Robocasting, Direct Ink Writing (DIW) and Freeze-form Extrusion Fabrication (FEF) (Cesarano et al, 2005;Doiphode et al, 2011;Fu et al, 2011;Lewis et al, 2006) and (ii) powder bed based, including Selective Laser Sintering (SLS), Selective Laser Melting (SLM) and 3D printing (3DP) (Goodridge et al, 2006;Liu et al, 2010;Marchelli et al, 2010;Seitz et al, 2005;Xiao et al, 2008;Kolan et al, 2011). Porous scaffolds made using extrusion based methods generally show higher compressive strength because of the smaller particle size used in the paste and the layer-by-layer deposition approach used to build the parts .…”
Section: Introductionmentioning
confidence: 99%